(Bi1/6Na1/6Ba1/6Sr1/6Ca1/6Pb1/6)TiO3-based high-entropy dielectric ceramics with ultrahigh recoverable energy density and high energy storage efficiency. Issue 10 (13th February 2023) - Wang, Hao; Zhang, Ji; Jiang, Shunshun; Wang, Jiajia; Wang, Jing; Wang, Yaojin
Abstract : The unique atom configuration in high-entropy dielectric ceramics gives rise to high P max, small P r . Accordingly, ultrahigh recoverable energy density of 8.8 J cm −3 and high η of 92.5%, as well as excellent thermal stability, are achieved. Abstract : Inspired by the development of high-power/pulsed-power techniques, dielectric capacitors with enormous power densities as well as ultrafast charge/discharge speeds have captured increasing attention and extensive research, particularly ceramic capacitors. Nevertheless, the limited recoverable energy density ( W rec ) and/or low energy storage efficiency ( η ) of ceramic capacitors delay their applications in capacitive energy storage. Herein, single phase high-entropy (Bi1/6 Na1/6 Ba1/6 Sr1/6 Ca1/6 Pb1/6 )Ti1− x Zr x O3 dielectric ceramics are designed and investigated. The enhanced dielectric relaxation behavior and fine grain size gave rise to decreased remnant polarization ( P r ) and promoted electric breakdown strength ( E b ). The special electronic structure of Pb 2+ and Bi 3+ favors retaining relatively large maximum polarization ( P max ). Accordingly, ultrahigh W rec of 8.8 J cm −3, high η of 92.5%, and exceptional thermal reliability ( W rec = 4.5 J cm −3 ± 6.5% in the range of 25–180 °C) are synchronously achieved in the optimum composition of x = 0.12, providing a feasible strategy to explore high-performance dielectric ceramics for applications in electrostatic energy storage.